FIELD CONTROL OF LEAF ROT DISEASE OF COCONUT WITH FUNGICIDES - N. Srinivasan; M. Gunasekaran (International Coconut Community Journal, 1996)
Leaf rot is a disease of fungal complex super imposed on root (wilt) affected coconut palms in India. A field fungicidal control trial on the disease involving contact (indofil M‑45, Fytolan) and systemic (Calixin) fungicides was conducted Fungicidal treatments, spraying of Indofil M‑45 and pouring of Calixin into axil of spindle, were found beneficial as the disease intensity reduced in newly emerged leaves. However, the extent of disease amelioration by fungicides was marginal to moderate level only. Importance of broad spectrum fungicide(s) and measures of disease protection are outlined.